2013
DOI: 10.3746/jkfn.2013.42.5.682
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cabbage Juice and Cabbage-Mixed Juice on the Growth of AGS Human Gastric Cancer Cells and on HCl-Ethanol Induced Gastritis in Rats

Abstract: This study determined the effects of cabbage juice and cabbage-mixed juices on the growth of AGS human gastric cancer cells and their anti-gastritic effects on HCl-ethanol induced gastritis in SD rats. Cabbage juice showed the highest growth inhibition on AGS gastric cancer cells in vitro (42%), compared with chlorella (20%) and kale juice (21%). However, cabbage-chlorella and cabbage-kale juice mixtures (at a 7:3 ratio) showed synergistic effects (57% and 65% inhibitory effects, respectively) on the gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(2 reference statements)
0
5
0
1
Order By: Relevance
“…The rats were given ad libitum access to feed and water. In experiments for inducing gastric ulcers, mice were administered their respective C. cassia extract article (except for the gastritis control groups, which were administered a carboxymethyl cellulose sodium salt (CMC) solution) after 48 h of feed deprivation, and gastric damage was induced by administering indomethacin (80 mg/kg) [ 51 , 52 ], ethanol (100% EtOH), or an ethanol-HCl (150 mM HCl in 70% EtOH) [ 11 , 12 ] 30 min after the pre-treatment. Five hours later, all animals were sacrificed, and their stomachs were extracted for experimental purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were given ad libitum access to feed and water. In experiments for inducing gastric ulcers, mice were administered their respective C. cassia extract article (except for the gastritis control groups, which were administered a carboxymethyl cellulose sodium salt (CMC) solution) after 48 h of feed deprivation, and gastric damage was induced by administering indomethacin (80 mg/kg) [ 51 , 52 ], ethanol (100% EtOH), or an ethanol-HCl (150 mM HCl in 70% EtOH) [ 11 , 12 ] 30 min after the pre-treatment. Five hours later, all animals were sacrificed, and their stomachs were extracted for experimental purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of therapeutic agents for gastritis and gastric ulcers using natural products, with no side effects, is in progress. Several studies have recently reported the protective effects of natural products without side effects and toxicity against gastric mucosal damage using several animal models [ 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2015) and inhibitory effects of cabbage juice on EtOH-HCl induced gastritis in rats (Hong et al. 2013) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EtOH/HCl causes severe damage and necrotic lesions to the gastric mucosa (Hong et al. 2013). The animal models of gastric injuries induced by indomethacin and EtOH/HCl have been widely used in studies to evaluate the protective effects of herbal products against gastritis and gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…가되었으나, 반면에 과도한 퇴비시용은 질산염 [2], 양분의 지 하수로의 용탈 [3] 및 이로 인한 지하수 오염 [4] [7]. 양배추는 간 보호 및 간기능 개선 [8], 항산화 활성 [9], 항위염 [10] 등의 효 과로 인해 케이크 [11], 떡 [12], 양배추 즙 [13] ---------------------------------------(%) ---------------------------------------…”
unclassified